Making Transport Work for Women and Men : Tools for Task Teams - World Bank (Washington, DC, 2013)
The primary objective of this report is to provide brief, relevant, and practical tools for World Bank task teams and their country counterparts to facilitate their work in addressing gender issues in transport policies and projects. This responds to the need, expressed by task teams, to repackage and condense existing gender and transport tools in formats more relevant to transport operations. These tools can also be used for training on gender and transport. The term tool was selected to convey the notion that these materials are nuts and bolts resources to be used when needed, and to emphasize that they are not requirements or directives.